Social and Philosophical Analysis of Political and Legal Status of the Occupation Regime in the Context of Struggle for Ukraine's Territorial Integrity - Tsiurupa, Mykhailo (Київський національний університет імені Тараса Шевченка, 2017)
The article is devoted to the complex analysis of complex socio-political and military-legal status of the occupationphenomenon that has become actualized in connection with the actual occupation of Crimea by Russian troops in 2014 and hiddenoccupation of Donetsk and Lugansk regions.The term "temporary occupation" used in Military Doctrine of Ukraine in 2015 should not be administered in confusion aboutthe disastrous and danger to the life of the nation, the country capture integral part of the territory of a sovereign state, abuse offreedom and spiritual heritage of its inhabitants. The experience of history, ending the occupation is only possible through the action ofsupport - spiritual and practical and effective when the occupant feels intolerance stay in a foreign land for him.Since the French Resistance Nazi occupation of France, philosophers, intellectuals showed an example of the "philosophy ofheroism", aimed to protect the gains of freedom and democracy of society, which is important for Ukraine.Based on complex political, legal and philosophical and humanitarian analysis we are trying to uncover a dangerousexistential nature of the occupation, which is that the foreign government not only captures the area of wealth, destroys culturalarchetypes thinking and "crippling" language, but also poses an existential threat the indigenous population of the territory, leads topartition the country and occupied oblivion.From a political and legal point of view of military occupation is a temporary phenomenon under international law and inaccordance with modern international law must not lead to the annexation of territory. Thus, the political and legal terms as occupationexacerbates the challenge of humanity in the territory temporarily occupied - like the minimum required level of cooperation to ensurethat essential needs. However, the spiritual dimension of occupation more difficult - it encourages collaboration, splitting the unity ofthe nation, artificially nasadzhaye alien cultural stereotypes. Only the consolidation of all patriotic forces, secular and religious, civicand government agencies and institutions under the slogan "Down with the occupiers" can save the country from splitting apart.Key words: political and spiritual resistance to the occupation, the legal status of occupation regime, the humanitarianaspect of the existential threat of occupation.

Стаття присвячена комплексному аналізові складного соціально-політичного та воєнно-правового статусу феномену окупації, який став актуалізований у зв’язку з фактичною окупацією Криму російськими військами з 2014 року та прихованою окупацією частини Донецької та Луганської областей. Термін «тимчасова окупація», який використовується у Воєнній доктрині України 2015 року не повинен вводити в оману відносно згубності та небезпечності для життя нації, цілісної країни захоплення частини території суверенної держави, знущання над свободою та духовним спадком її жителів. З часів французького Опору фашистській окупації Франції філософи, інтелектуали показали приклад «філософії героїзму», спрямованої за захист завоювань свободи і демократії всього суспільства, що актуально для сучасної України. Тільки консолідація всіх патріотичних сил, світських і релігійних, громадських та державних установ та інституцій під гаслом «Геть окупантів» може врятувати країну від розколу на частини.Ключові слова: політичний та духовний опір окупації, правовий статус режиму окупації, гуманітарний аспект, екзистенційні загрози окупації.
Соціально-філософський аналіз політико-правового статусу режиму окупації в контексті боротьби України за територіальну цілісність